Goodbye China: What Do Fewer Foreigners Mean for Multinationals and the Chinese Economy? - Frank Bickenbach; Wan-Hsin Liu (Intereconomics, 2022)
The number of foreigners living in China is very low in international comparison and has further declined recently. While the strict COVID-19-related travel restrictions played a major role in this decline, there are indications that the decline started in part before the pandemic and may well continue once the pandemic-related restrictions are lifted. Against this background, this article discusses the economic challenges that the reduction in the number of foreigners is causing for Western multinationals operating in China and to the Chinese economy more generally. The consequences could spill over to the world economy and reinforce economic and technological decoupling tendencies between China and the West.
Keywords: J61; F23; 330